Animal Labor: A New Perspective on Human-Animal Relations - Estebanez, Jean; Porcher, Jocelyne (transcript, 2019)
Do animals work? Is it possible to work with animals without exploiting them? Might animals even be empowered through work? This provocative collection offers original answers to these questions and allows readers to think about human relationships with domestic animals beyond the well-trodden tropes of domination or animal welfare. To study animal work means to look at animals in new ways and to discover in them unsuspected skills and knowledge that open up new ethical and political horizons.